Assessing avian richness and diversity in different regions of oil palm plantation in Selangor, Malaysia - Amir, Aainaa; Mohd Noor, Hafidzi; Hambali, Kamarul (SciPress, 2015)
Malaysia is characterized by a variety of habitats such as forests, clearings, thickets, and cropland that attract various species of birds. This study examined the bird community in terms of richness and diversity at oil palm plantations habitat. The abundance of birds was determined by using distance sampling point count method. A total of 2722 birds belonging to 38 families representing 86 species of birds were detected. Diversity analysis indicates that the species of birds in the oil palm plantation at Sungai Pelek is more diverse (Shannon-Wiener Diversity Index H; 3.52) and richness (Margalef’s Richness Index R1; 10.2) than oil palm plantation in Teluk Panglima Garang-Pulau Carey and Banting-Jenjarum. However, the species of birds in the oil palm plantations at Teluk Panglima Garang-Pulau Carey and Banting-Jenjarum show higher evenness (Pielou’s Evenness Index E; 0.82) compared with oil palm plantations in Sungai Pelek. The results of this study indicate that the species composition and distribution of the avian species in the oil palm plantations are affected by habitat characterization of that particular area and its vicinity.